PEMANFAATAN MEDIA SOSIAL DALAM MENINGKATKAN PENJUALAN USAHA KERAJINAN GERABAH PADA MASA PANDEMI COVID – 19 - Ida Ayu Susan Trisna Diatmika; Afif Syarifudin Yahya (Gapenas Publisher, 2021)
Banyuning Village is a center of pottery craft suppliers in Buleleng Regency. The pottery craft is usually used for traditional ceremonies and souvenirs. The pandemic Covid-19 has reduced the sales of craft. The purpose of community service activities is to help pottery artisans to increase sales during pandemic Covid-19 through used social media. The methods used are surveying pottery artisans not yet on social media, giving education utilization and profits using social media, product marketing the social media, and the monitor. The result shows that social media platforms important role in increasing sales during the pandemic Covid-19. Optimizing social media as product marketing can increase sales of pottery products up to 60% and reach the consumer on a broader scale